Clinical Uses of Melatonin in Pediatrics - Emilio J. Sánchez-Barceló; Maria D. Mediavilla; Russel J. Reiter (Hindawi Limited, 2011)
This study analyzes the results of clinical trials of treatments with melatonin conducted in children, mostly focused on sleep disorders of different origin. Melatonin is beneficial not only in the treatment of dyssomnias, especially delayed sleep phase syndrome, but also on sleep disorders present in children with attention-deficit hyperactivity, autism spectrum disorders, and, in general, in all sleep disturbances associated with mental, neurologic, or other medical disorders. Sedative properties of melatonin have been used in diagnostic situations requiring sedation or as a premedicant in children undergoing anesthetic procedures. Epilepsy and febrile seizures are also susceptible to treatment with melatonin, alone or associated with conventional antiepileptic drugs. Melatonin has been also used to prevent the progression in some cases of adolescent idiopathic scoliosis. In newborns, and particularly those delivered preterm, melatonin has been used to reduce oxidative stress associated with sepsis, asphyxia, respiratory distress, or surgical stress. Finally, the administration of melatonin, melatonin analogues, or melatonin precursors to the infants through the breast-feeding, or by milk formula adapted for day and night, improves their nocturnal sleep. Side effects of melatonin treatments in children have not been reported. Although the above-described results are promising, specific studies to resolve the problem of dosage, formulations, and length of treatment are necessary.